L’approccio dell’Unione Europea relativo alla neutralità di genere nel linguaggio - Rega, Lorenza (Linguistik Online, 2024)
Equality is considered one of the pillars of the European Union. This article analyzes a number of EU texts with the aim of examining how equality relates to gender neutrality in language. More specifically, the study tries to verify if disregarding gender neutrality may be a form of discrimination and whether progress has been made in this area. The article also mentions the problem of reverse discrimination in language (as in Hebamme/ Entbindungspfleger), which found a positive solution in the Gesetz zur Reform der Hebammenausbildung und zur Änderung des Fünften Buches Sozialgesetzbuch. The road to linguistic equality is still long, and the significant role played by linguistic sensitivity is made even more complex by the need to apply language neutrality when referring to the LGBTI community.